2020
DOI: 10.1111/1440-1681.13310
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic pseudogene DUXAP10 knockdown suppresses proliferation and invasion and induces apoptosis of papillary thyroid carcinoma cells by inhibition of Akt/mTOR pathway

Abstract: Pseudogenes, another novel group of non‐coding segments without protein‐coding capacity, are closely associated with tumourigenesis and cancer progression. Double homeoboxA pseudogene 10 (DUXAP10) is reported to be robustly expressed in thyroid carcinoma. However, the functional role and underlying mechanism of DUXAP10 in papillary thyroid carcinoma (PTC) progression remain undefined. DUXAP10 expression in PTC cells was detected by qRT‐PCR. Cell proliferation and invasion were determined using 3‐(4,5‐dimethyl‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…By modulating the Wnt/β-catenin and PI3K/Akt signaling pathways, DUXAP10 has been demonstrated to influence the invasion and migration of HCC (Han et al, 2019) SMMC-7721 and HepG2 cells through the regulation of EMT. A previous study of PTC also demonstrated that DUXAP10 was involved in increasing cell invasion and migration and regulating EMT via activation of the Akt/mTOR (Li et al, 2020) pathway. Additionally, DUXAP10 was found to play a crucial role in GC (Xu et al, 2018) cell invasiveness and migration by interacting with the RNA-binding protein HuR and subsequently stabilizing β-catenin mRNA.…”
Section: Cell Invasion and Migrationmentioning
confidence: 83%
See 3 more Smart Citations
“…By modulating the Wnt/β-catenin and PI3K/Akt signaling pathways, DUXAP10 has been demonstrated to influence the invasion and migration of HCC (Han et al, 2019) SMMC-7721 and HepG2 cells through the regulation of EMT. A previous study of PTC also demonstrated that DUXAP10 was involved in increasing cell invasion and migration and regulating EMT via activation of the Akt/mTOR (Li et al, 2020) pathway. Additionally, DUXAP10 was found to play a crucial role in GC (Xu et al, 2018) cell invasiveness and migration by interacting with the RNA-binding protein HuR and subsequently stabilizing β-catenin mRNA.…”
Section: Cell Invasion and Migrationmentioning
confidence: 83%
“…PTC is the most common type of thyroid carcinoma (Li et al, 2018;Hu et al, 2019;Wang et al, 2021a). DUXAP10 was first confirmed by Li et al (2020) to be highly expressed in PTC tissues and TPC-1, BCPAP, K1, and IHH-4 cells compared with adjacent normal thyroid tissues. In addition, DUXAP10 has been demonstrated to contribute to protumorigenic effects by promoting BCPAP and K1 (Li et al, 2020) cell proliferation and invasion in addition to inhibiting cell apoptosis.…”
Section: Thyroid Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that the pseudogenes BRAF and DUXAP10 are dysregulated in thyroid carcinoma ( 10 , 32 ). Consistent with these findings, the current study indicated that LGMN was upregulated in thyroid carcinoma, and that this increase in expression was associated with a poorer outcome.…”
Section: Discussionmentioning
confidence: 99%